Optimization of the Central Cooling System on the Main Engine at MV. Meratus Amurang - Mursidi, Mursidi; Triyanto, Andry Bagus (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
The cooling system is equipped in the engine for cooling and preventing overheating, the cooling system in addition to aiming for this, is required to regulate and stage the optimal temperature in the engine operating by flowing the cooling medium for the parts of the engine to be cooled, the system Cooling must also be considered so that the engine can operate properly, one of the components of the cooling system is a heat exchanger which has a very important role in supporting the performance of the cooling system. A heat exchanger is a device in which heat transfer occurs between two or more fluids at different temperatures. This research was carried out on board the MV. Meratus Amurang. The cooling system used on the MV Meratus Amurang is a centralized cooling system (Central Cooling), this cooling system is designed to have only one heat exchanger which Teknologi Rekayasa Permesinan Kapal is cooled by seawater, while for other coolers including jacket water, lubricating oil, rinse air, cooled with low temperature fresh water. The purpose of this study is to find out how to perform maintenance and operation of the cooling system on the main engine on board the MV. Meratus Amurang.